Martin Luther's Table talks - Luther, Martin, 1483-1546 (Luther's Works., 2017)
This volume provides access to selections from Martin Luther s Table Talk, Volume 54 of Luther s Works. Editor Henry F. French has carefully chosen some of the best of Luther s conversations with many guests who frequented the dinner table in the home of Martin and Katie Luther. Following the afternoon supper served at around 5 p.m. in the Luther household, guests ranging from exiled clergy, escaped nuns, government officials, visitors from abroad, and colleagues of Luther in the University stayed on in the relaxed and hospitable atmosphere to engage in spirited conversation. From 1531 till the year Luther died in 1546, colleagues and friends took notes of the table conversations in the Luther home. Topics ranged widely as Luther commented on his personal life and family; his perspectives on theology, Scripture, and the life of faith; his comments on political and social topics; and more. Almost no current issue was "off the table." Those who read this book will join the conversation with Luther and friends as they wrestle with important questions of the day. Pull up a chair and join the circle. Henry F. French has written a brief new preface to introduce this abridged volume.